Deteksi Dini Dan Edukasi Kesehatan: Pencegahan Kecanduan Gadget Pada Anak Usia Pra Sekolah - solikah, siti nur; Sakitri, Ganik (Politeknik Indonusa Surakarta, 2025)
The advancement of technology has significantly facilitated children's access to information and entertainment. However, it has also increased the risk of gadget addiction across all age groups. Preschool children who excessively use gadgets are more likely to experience social, emotional, and cognitive developmental disorders. Prolonged gadget use can negatively impact both their physical and psychological development. This community service program aimed to conduct early detection of gadget addiction and provide education to parents regarding its negative impacts and preventive measures. The program was implemented through educational sessions for parents, children, and teachers at TK Budi Karya Surakarta on November 20, 2024. A total of 20 parents participated in the session. The results indicated an improvement in parental understanding after the educational intervention, as evidenced by an increase in the average post-test score (94.2) compared to the pre-test score (87.5). In conclusion, educating parents on healthy gadget use for preschool children is crucial in preventing gadget addiction and supporting children's overall well-being.